DIE LEWENSWYSE VAN DIE SUID AFRIKAANSE JEUG VANAF 1652 TOT VOOR DIE VOORTREKKERTYDPERK - Le Roux, A.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
The lifestyle of the South African Youth from the year 1652 up to the Voortrekker era is depicted in this article. Conditions during these pioneering days are sketched as well as problems on the Eastern frontier, the role of the 1820 Setlers and the enormous problems presented by the Xhosas.